2016
DOI: 10.5114/aoms.2016.59268
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of deterioration of lung function in Polish children with cystic fibrosis

Abstract: IntroductionSeverity of lung disease varies in patients with the same CFTR genotype. It suggests that other factors affect the severity of cystic fibrosis (CF). The aim of the study was to identify risk factors that determine lung function decline in Polish cystic fibrosis children.Material and methodsThe follow-up time was no less than 5 years of respiratory status observation based on the forced expiratory volume in 1 s value (FEV1). The socio-economic data, perinatal interview, presence of meconium ileus (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Prediabetes was one of the most relevant predictors of deterioration of lung function defined as a significant decrease in FEV1 predicted value, during a 5 year-follow-up ( 17 , 18 ) (evidence Moderate).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prediabetes was one of the most relevant predictors of deterioration of lung function defined as a significant decrease in FEV1 predicted value, during a 5 year-follow-up ( 17 , 18 ) (evidence Moderate).…”
Section: Resultsmentioning
confidence: 99%
“…Among prediabetes, IGT represents one of the most relevant predictors of the decline in pulmonary function ( 17 ) ( 18 ) and both CFRD and IGT have been recognized as independent risk factors for pulmonary exacerbations and colonization by common CF pathogens, in particular by Pseudomonas Aeruginosa , and its form of infection characterized by multi-resistance to antibiotic therapy and co-infection with other pathogens ( 11 , 16 , 19 , 21 23 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent Polish study found that early P. aeruginosa chronic colonization was a predictor of lung function deterioration (p=0.0165) among other risk factors (presentation of meconium ileus, impaired glucose tolerance, number of exacerbations), contrary to time of diagnosis and type of CFTR mutation. 30 In Tunisia, lung function tests are difficult to perform in children due to their limited availability. Monitoring of the microbiology sputum examinations is often irregular and the analysis is limited to the exacerbation period.…”
Section: Discussionmentioning
confidence: 99%
“…Before we begin to describe the different treatment options for CFRD and cystic fibrosis-associated prediabetes, an important premise needs to be made: the therapy of the different forms of glucose derangement has a favourable impact not only on strictly metabolic outcomes but also, and above all, on the morbidity and complications associated with cystic fibrosis. In particular, a favourable impact on pulmonary function, growth, nutritional status and the recurrence of respiratory infections has been demonstrated [11][12][13].…”
Section: Therapymentioning
confidence: 99%